Hepatitis A and hepatitis E virus co-infection with right pleural effusion, ascites and acute acalculous cholecystitis. A case report - iza Palacios, Luis (2020)
Hepatitis A and hepatitis E are the leading causes of acute viral hepatitis in developing countries due to our poor sanitaryconditions, both spread by fecal-oral route or through contaminated water and food. Being both self-limiting diseases, they are usually benign but may present with atypical clinical findings. A 32 year-old female with right pleural effusion, ascites and acalculous cholecystitis during the course of HAV and HEV co-infection is reported. Clinical improvement was observed with conservative management. As far as we know, this is the first case described of a patient with these three complications in thebackground of a hepatitis A virus and hepatitis E virus co-infection.